Inkjet Printed Negative Supercapacitors: Synthesis of Polyaniline‐Based Inks, Doping Agent Effect, and Advanced Electronic Devices Applications. (12th February 2014) - Chiolerio, Alessandro; Bocchini, Sergio; Porro, Samuele
<x xml:space="preserve">Abstract</x> Low frequency negative supercapacitors and high frequency negative capacitors are realized developing a polyaniline (PANI) based ink for piezoelectric inkjet printers, water based. PANI is synthesized by oxidation polymerization starting from the aniline dimer, thus avoiding the use of a toxic/mutagen substance such as aniline. In order to work in aqueous phase, the reverse addition of the dimer in the oxidative solution is made. The chlorinated emeraldine salt of PANI is produced and emeraldine base is prepared by dedoping. Two different doped PANI solutions are produced by solubilization of the emeraldine salt in dimethylsulphoxide and addition of respectively trifluorosulfonic acid and camporsulfonic acid, and then used as inks for the fabrication of inkjet‐printed tracks of different geometries. The properties of inkjet‐printed devices are characterized both in DC and AC regimes, showing very good performances under specific measurement conditions in terms of conductivity, as well as extremely interesting phenomena whose origin is still under debate, such as low frequency negative supercapacitance, high frequency negative capacitance and negative resistance. The realization of the highest negative supercapacitance realized so far, of –2.3 mF @ 30 Hz, corresponding to a specific mass capacity of –799 F g−1, is reported.